Thermal radiation effect on MHD stagnation point flow of Williamson fluid over a stretching surface - Hasmawani, Hashim; Muhammad Khairul Anuar, Mohamed; Nazila, Ishak; Norhafizah, Md Sarif; Mohd Zuki, Salleh (IOP Publishing, 2019)
Thermal radiation effects on MHD stagnation point flow of Williamson fluid over a stretching surface are studied. With the help of similarity transformation, the governing equations are converted to nonlinear ordinary differential equations and then solved numerically by Runge-Kutta-Fehlberg (RKF) technique. Numerical results for the reduced Nusselt number and reduced skin friction coefficient as well as the temperature and velocity profiles are elucidated through tables and graphs. The influence of Prandtl number, stretching parameter, Williamson fluid parameter, thermal radiation parameter and magnetic parameter are analyzed and discussed. It is found that, as Prandtl number and magnetic parameter increase, the temperature profiles decrease. Meanwhile, as Williamson fluid parameter and thermal radiation parameter decrease, the temperature profile increase.